THE INFLUENCE OF CELEBRITY ENDORSEMENT ON CONSUMER PURCHASE INTENTION (CASE STUDY : CLEAR SHAMPOO IN MANADO - Wo’en, Angela Z. (Sam Ratulangi University, 2016)
Clear shampoo occupied the first position of the best brand shampoo in 2015 with 22.1%. In 2005 Unilever developed ClearÂ strategy for the brand extension to the hair styling category. Companies should be able to designing an effective marketing strategy so that consumers can give a positive response to the product. The role of celebrity endosement is often used to support the product and it helps build trust with current and potential costumers, increases the chance of the brand being remembered, and attract new type of audience. This research used a multiple linear regression analysis with the sample is 100 respondents that were obtained from citizen at Manado City. The result from this research shown that the physical attractiveness, expertise, and congruity have significantly influence customer purchase intention to buying Clear shampoo. The consumer like the endorser that always shows up on the television and already recognize by the consumer, in other words the consumer like the endorser that already have a high popularity and also the respondent more attracted by a good looking endorser.